(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
The study introspected stakeholder’s perspectives on Zambia’s competence-based curriculum. This study was guided by an interpretive paradigm, employing qualitative interpretive phenomenology study design. Data was collected using observation and semi-structured interview guide with twenty participants who included teachers, school administrators, policymakers, and curriculum developers which was analysed thematically. The study revealed that Competence-Based Curriculum carries a liberal and inclusive approach, alignment with socio-economic needs, bridging the skill gap and enhanced career pathways to meet diverse learners. On the other hand, the study revealed that the new curriculum framework may face implementation challenges, such as inadequate resources, insufficient teacher training, and resistance to change, which will hinder its effectiveness. To address the projected implementation pitfalls of Zambia’s Competence-Based Curriculum, stakeholders must ensure adequate teacher training, resource allocation, continuous monitoring, and inclusive policy adjustments based on practical challenges and feedback. Therefore, transitioning to a Competence-Based Curriculum is a strategic move for Zambia, aiming to produce skilled, adaptable, and responsible citizens ready to contribute to national development and succeed in the global arena. Based on these findings, the study recommends that fully realize the CBC, Zambia must invest in capacity building, infrastructure development, and continuous stakeholder engagement.